Respiratory and nasal symptoms, immunological changes and lung function among petroleum refinery workers - Jordan Minov; Jovanka Karadzinska-Bislimovska; Kristin Vasilevska; Lidija Trajceva; Snezana Risteska-Kuc; Saso Stoleski; Dragan Mijakoski (Società italiana di medicina del lavoro, 2010)
Objective: To assess adverse respiratory effects and immunological changes among petroleum refinery workers. Methods: We performed a cross-sectional study including 80 subjects employed in the coking unit of a petroleum refinery (54 males and 26 females, aged 28-56 years, duration of exposure 7-28 years) and an equal number of office workers, matched by sex, age and smoking habits. Asthma and allergic rhinitis diagnosed by a physician, as well as respiratory and nasal symptoms in the last 12 months, were recorded by questionnaire. Evaluation of the subjects under study also included skin prick tests for common inhalable allergens and lung function tests. Results: We found a similar prevalence of asthma and allergic rhinitis in both examined groups. Prevalence of overall respiratory symptoms was higher among petroleum refinery workers (33.7% vs. 22.5%) with a statistically significant difference for cough (30.0% vs. 13.7%, p=0.018) and wheezing (21.1% vs. 8.6%, p=0.029). Prevalence of overall nasal symptoms was higher among petrol refinery workers (36.2% vs. 23.7%) with a statistically significant difference for runny nose (28.7% vs. 12.5%, p=0.014).We found a similar prevalence of allergic sensitization to common inhalable allergens in both examined groups. The results of lung function tests showed significantly lower value of MEF50 (61.9% vs. 67.4%, p=0.019) and MEF75 (56.1% vs. 62.9%, p=0.000) among petroleum refinery workers. Respiratory impairment was observed in both smoking and non-smoking petroleum refinery workers. Conclusion: Our data suggest that workplace exposure among petroleum refinery workers may lead to respiratory and nasal symptoms and lung function impairment.
Keywords: Refinery; respiratory effects; immunological changes